Analysis of the values of Islamic Education in the Worship Traditions of Muslims in Indonesia: An Ethnographic Study of Congregational Groups Sumbayang Ampek Puluah Hari - Putri, Amelisa; Akmal, Hermiza; Syafitri, Junita (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
The Forty days of prayer the fardhu prayer in congregation for forty consecutive days which is usually done by Syattariyah congregation. In its implementation, there is a very interesting uniqueness to discuss. The purpose of this research is to analyze how the implementation of the tradition that have been waiting for dozens of days and describe the educational values ​​contained in it. This research focuses on the implementation that have been waiting for for a dozen days in Nagari Singgalang. Method used in this study is a qualitative method with an ethnographic approach. Data sources were taken from ten informants consisting of two priests and eight congregations with individual and group interviews. To strengthen the research data the authors also made direct observations. All informants are people who are actively involved in the implementation that have been waiting for for dozens of days. All data from interviews and observations were analyzed using the Milles & Huberman Interactive Analysis model. Research findings shows that: the first, which have been waiting for tens of days for was first introduced by Sheikh Buya Tanjung Medan around 1100 Hijriyah. Second, have been waiting for dozens of days for the legal basis for its implementation. This is based on the hadith of the Prophet Muhammad narrated by Imam At-Tirmidhi. Third, the implementation that have been waiting for dozens of days is the same as the congregational prayers in general, but every fardhu prayer is added with the qadha congregational prayer as well. Fourth, the values ​​of Islamic education contained in the implementation of the Sumbayang Ampek Puluah hari are spiritual values, social values, disciplinary values, cultural values, and integrity values. The results of this study can be used as information to the public in order to be able to understand the existing problems.